Ultracold collisions for Bose-Einstein condensation - Butcher, L; Stacey, D; Foot, C; Burnett, K (1999)
We describe the low-energy scattering theory relevant to the description of the Bose-Einstein condensed gases recently produced using evaporative cooling. We examine the validity range of the approximations being used to describe the ultracold interactions in the context of the interaction between caesium atoms at the temperatures produced by evaporation in a magnetic trap. We discuss the prospects for future developments in the field.